Gender (A)Symmetry in Correlates of Perpetration of Intimate Partner Violence: Gender (A) Symmetry in IPV and the Role of Gender Attitudes. (July 2020) - Yoshihama, Mieko; Blazevski, Juliane; Bybee, Deborah
This study examined, using structural equation modeling (SEM), gender differences and similarities in correlates of the perpetration of emotional aggression against intimate partners among one of the largest groups of Asian Indians in the United States, Gujaratis. Although most of the correlates of emotional aggression (e.g., patriarchal attitudes, spousal disagreement, and alcohol use) were similar for men and women, higher support for gendered domestic roles was significantly related to higher perpetration of emotional aggression for men but not for women. Multigroup latent SEM served as a unique analytical strategy to investigate gender (a)symmetry, a controversial but critical debate in the field.